O Apocalipse siríaco de Daniel. São Paulo: Paulinas, 2017. - Silva, Ângelo Vieira da (2019)
Resenha acadêmica de:RAMOS, Marcos Vinícius. O Apocalipse Siríaco de Daniel. São Paulo: Paulus, 2017. 120 pp. ISBN  978-85-349-4496-0.